Port Marketing. Eine Bestandsaufnahme. - Sorgenfrei, Jürgen (Deutscher Verkehrs-Verl., 2009)
Hafenmarketing oder "Port Marketing" wird für deutsche Seehäfen seit vielen Jahrzehnten betrieben. Die Zielsetzungen dieser Aktivitäten werden näher betrachtet. Im Anschluss daran wird der relevante Markt für das Port Marketing analysiert und die wesentlichen Einflussfaktoren werden herausgestellt. Aufbau und Organisation des Port Marketings in Deutschland beschreibt der dritte Teil. Im letzten Kapitel werden die zukünftigen Herausforderungen für das Hafenmarketing analysiert und notwendige Anpassungsmaßnahmen diskutiert.

The worldwide maritime transport market has witnessed considerable change in recent years. Market concentration and growing containerization in the general cargo sector have fundamentally changed Germany's port marketing conditions. In order to ascertain marketing efficiency objectively, individual ports' relevant market conditions need to be identified with the help of an analysis of all the pertinent factors. Historical aspects have been relied upon to portray the situation and status of marketing at North German ports. Looking into the future, an analysis is made of the need for port marketing to adapt to a changed environment. There is a need for market-oriented management and for the implementation of a new marketing approach. This is the only way to guarantee success for port marketing in future.
Port marketing in Germany.
Keywords: Verkehr; Hafen; Hafenstadt; Standort; Seehafen; Gebrochener Verkehr; Güterverkehr; Marketing; Wasserverkehr; Verkehrswirtschaft; Wirtschaftsentwicklung; Logistik; Hinterlandverkehr; Hafenwirtschaft